Challenges of young agripreneurs in Eastern Bhutan / Tashi Dendup, Rekha Chhetri and Choeying Dolma - Dendup, Tashi; Chhetri, Rekha; Dolma, Choeying (Research Management Centre (RMC), 2021)
Bhutan encourages youth to engage in agribusiness. However, many young Bhutanese not pursuing agribusiness indicates the prevalence of challenges that remain unaddressed. These challenges must be understood adequately in order to not only encourage but retain the youth entering into the agribusiness sector. Bhutan has a scarcity of research on the challenges faced by young agripreneurs; therefore, this study initiated the filling of this gap. This study was conducted in Mongar, Trashigang, and Trashiyangtse districts of Eastern Bhutan. Data were collected from 50 registered young agripreneurs in these districts using a self-administered semi-structured questionnaire. The results showed that young agripreneurs were challenged most by environmental issues (82%), followed by inaccessible financial supports (80%), and management issues (58%). Although 56% of the young agripreneurs indicated that they generally faced marketing challenges, the number was 10% less at present than when they initially started their business. Access to land and farm inputs (overall) were not a problem for many young agripreneurs. Accordingly, to promote agribusiness, this study recommends relevant authorities to support the establishment of enabling business environments for young agripreneurs by training them in climate-smart agriculture, the provision of micro-credits, and improving their access to enterprise management training, such as leadership.